2012
DOI: 10.5402/2012/762920
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antioxidant Treatment on Fibrogenesis in Rats with Carbon Tetrachloride-Induced Cirrhosis

Abstract: Aim. This study aimed to assess the antioxidant activity of quercetin (Q) in an experimental model of cirrhosis induced by CCl4 inhalation. Materials and Methods. We used 25 male Wistar rats (250 g) that were divided into 3 groups: control (CO), CCl4, and CCl4 + Q. The rats were subjected to CCl4 inhalation (2x/week) for 16 weeks, and they received phenobarbital in their drinking water at a dose of 0.3 g/dL as a P450 enzyme inducer. Q (50 mg/Kg) was initiated intraperitoneally at 10 weeks of inhalation and las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
29
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 32 publications
9
29
0
Order By: Relevance
“…The presence of necrotic foci, fibrotic nodules, the infiltration of lymphocytes, and the fatty changes in liver cells are typical characteristic after the induction of cirrhosis (5,33) . The two experimental models used in this study reinforce and confirm the onset of liver damage and cirrhosis of the liver with consequent changes in gas exchange.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of necrotic foci, fibrotic nodules, the infiltration of lymphocytes, and the fatty changes in liver cells are typical characteristic after the induction of cirrhosis (5,33) . The two experimental models used in this study reinforce and confirm the onset of liver damage and cirrhosis of the liver with consequent changes in gas exchange.…”
Section: Discussionmentioning
confidence: 99%
“…The superoxide anion and the hydroxyl radical are involved in liver damage resulting from lipid peroxidation and interstitial matrix degradation 8 . Bona et al 9 report that a significant increase in serum levels of aspartate aminotransferase (AST) and alanine aminotransferase (ALT) after inhalation of chloroform in rats was reversed with quercetin administration, supporting the notion that quercetin has antioxidant and hepatoprotective effects. Also, it has been shown that the use of quercetin significantly reduces the biochemical alterations caused by cirrhosis, increasing survival in animals with secondary biliary cirrhosis.…”
Section: Introductionmentioning
confidence: 91%
“…The duration of treatment and the administration route may interfere with the hepatoprotective effect of quercetin. Miltersteiner 3 , Bona et al 9 and David et al 23 found positive results with intraperitoneal administration of quercetin. Behling et al 6 and Bona et al 9 used periods of 28 days and six weeks respectively.…”
Section: Effects Of Quercetin On Partial Hepatectomymentioning
confidence: 99%
See 2 more Smart Citations